PERAN DAKWAH JAMAAH HADRAH AL-FALAH DALAM MENINGKATKAN AKTIVITAS REMAJA MASJID DESA SUKADANA ILIR KECAMATAN SUKADANA KABUPATEN LAMPUNG TIMUR TAHUN 2019 - Nurtriantoro, Sapto; Sabdo, Sabdo; Islahudin, Ahmad Noor (Universitas Muhammadiyah Metro, 2020)
Islam is a da'wah religion of da'wah, it means a religion that always encourages its adherents to always actively broadcast Islamic teachings. Even the back and forthof Muslims really depends on the da'wah activities they do. Da'wah can be done byverbal, bil qalam, bil hal and it can be through various forums as long as the goalis the same, namely to invite to carry out Allah commands in the form of faith andto imitate His apostles. Through da'wah filled with remember to Allah, praising theProphet with the accompaniment of hadrah music will captivate the public,especially teenagers, to participate in religious activities carried out by the hadrahcongregation. This research uses descriptive qualitative research. Collecting data usingobservation, interviews, and documentation. Through interviews and observationsit was found that the main subjects studied were teenagers who were either membersof the congregation of hadrah Al-Falah itself. And successful da'wah is preachingthat has the right knowledge and manhaj that is straight, in accordance with the AlQur'anandAs-Sunnaheventhoughlust,reasonandmosthumansdiffer. The results showed that, the activities of calling, inviting and inviting da'wah wereonly one of the three activities that increased religious awareness in adolescents,namely the activity of inviting da'wah. Da'wah activities are different from callingand inviting, calling and inviting which are only used by invitation and throughconversation. However, the activities of da'wah invited Jama'ah Hadrah Al-Falahto combine the two activities, namely inviting mosque youths indiscriminately tolearn about good and correct religion together. And next, in increasing religiousawareness, there was only one of the eight mosque youths who experienced anincrease in religion, namely the builder of the congregation of hadrah al-falah. Sothis has an impact on the weak implementation of religious values in adolescents,where only 0.12% can implement religious values in society and the remaining 99.88% still need to improve learning related to understanding the content andmeaning contained in the maulid book. al-barzanji.